LEGAL DEVELOPMENT CONCEPT STRATEGY AND ITS ROLE IN THE MARKET ECONOMIC SYSTEM - Imelda Mardayanti (Journal of International Islamic Law, Human Right and Public Policy, 2024)
This study addresses the following questions: 1) Is the market economy system working well; and 2) What is the role of law in a market economy and what does pro-market legal development look like? This research is intended to collect secondary data through a literature search of legal materials relevant to legal and economic theories, which is currently conducted using qualitative analysis. This research was conducted using the juridical-normative method and with an analytical descriptive approach. Furthermore, this research comes to the conclusion that a market economy is an economy in which people are free to pursue the highest possible financial gain. Since people are the focus of all economic systems, the government has no function in the economy. However, the government, which in this case serves to regulate laws, is necessary for the market economy to function properly. Without this, the market economy will contract. Without the help of laws, especially economic laws, the market economic system can never function properly to generate wealth and prosperity.